Fulminant Disseminated Intravascular Coagulation as Initial Presentation of BRAF-Mutated Melanoma. (9th April 2019) - Chuang, Jeremy; Uche, An; Gupta, Rohan; Margolin, Kim; Kim, Phyllis
Abstract : Acute disseminated intravascular coagulation (DIC) is a pathological process involving dysfunction of the coagulation cascade. In this case report, we discuss a 33-year-old woman with BRAF V600E-mutated metastatic melanoma who presented in fulminant DIC with concurrent hemorrhagic and thrombotic manifestations and discuss the patient's brief response to combination therapy. In our discussion, we highlight the current understanding of DIC and also identify opportunities for future research to elucidate the genetic aberrations in melanoma that may result in treatment resistance to combination therapy.